Dress Syndrome Associated to Carbamazepine: Case Report (Revista de Medicina Clinica, 2025)
DRESS syndrome is a drug reaction with eosinophilia and systemic symptoms with an estimated incidence of 1 in 1,000 to 10,000. The case of a 42-year-old female who was admitted with a generalized dermatosis that evolved into acute liver failure, identified as DRESS syndrome, progressing to acute heart failure with the need for orotracheal intubation; She had a 40 day hospital stay, where she evolved favorably with normalization of liver enzymes. The objective of this case is the recognition of the syndrome for proper management and reduction of morbimortality.
Keywords: Drug Hypersensitivity Syndrome; Carbamazepine; Cytomegalovirus; Acute liver failure